Karakteristik Fisik dan Sensori Velva Kombinasi Puree Sirsak (Annona muricata L.) dengan Kulit Buah Naga Merah (Hylocereus polyrhizus) - Sophia Grace Sipahelut (Universitas Djuanda, 2023)
Velva is a frozen dessert containing low-fat, high natural fiber, and vitamin C from fruit raw materials. This study aims to determine the best formulation for making Velva using soursop puree and red dragon fruit peel puree. A completely randomized design was used as a research design with one factor, namely the ratio of soursop puree and red dragon fruit peel, which included four treatment levels, namely 90: 10; 80: 20; 70: 30; and 60: 40, with three repetitions. Physical test observations included overrun, melting power, pH, and sensory tests, including hedonic and hedonic quality tests for color, aroma, taste, texture, and overall. The de Garmo Effectiveness Index test is used to determine the best formulation. The results showed that the comparison of soursop puree and red dragon fruit peel puree had a significant effect on the physical and sensory characteristics of the velva, except for the hedonic quality of the aroma. Based on the de Garmo effectiveness index test, the best formulation was obtained from the soursop puree and red dragon fruit peel puree formulations 60%: 40% (effectiveness value 0.813) with an overrun value of 12.48%, melting power of 11.00 minutes/5 g, pH 5.45, pink in color, slightly soursop taste, slightly soursop scent, and soft texture, while the hedonic test results showed a value of like to like the color, aroma, taste, texture and overall.